Fusarium equiseti in tomato plants in Pernambuco State, Brazil - Lima, Débora Maria Massa (Pesquisa Agropecuaria Brasileira, 2014)
Wilt of tomatoes caused by Fusarium equiseti (Corda) Sacc. was observed at Bezerros, Camocim de São Félix and Lajedo, in Pernambuco State, Brazil. Initial symptoms are chlorosis and necrosis of the leaves. Discolouration of the vascular tissue was observed in the infected plants. The pathogenicity of the isolated fungus was proved through artificial inoculations. This is the first report on the occurrence of F. equiseti in tomato in Brazil.